2021
DOI: 10.3390/polym13071039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Process Parameters on the Adhesive Strength of Dissimilar Polymers Obtained by Multicomponent Injection Molding

Abstract: The growing demand in the consumer market for products with sustainable technologies has motivated new applications using overmolded natural fiber composites. Therefore, studies have been conducted mainly to understand the adhesive properties of overmolded parts. In the present study, a polypropylene (PP) composite with 30% coconut fibers without additives was developed with the aid of a corotating twin screw extruder. Subsequently, a multicomponent injection mold was developed based on the geometry of the ISO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…From the viewpoint of molding conditions, the higher cylinder temperature and higher injection speed increased lap shear strength. Pisanu et al [16] also reported that higher holding pressure, cylinder temperature and injection speed increased the joining strength.…”
Section: Influence Of Molding Conditions and Cnf Content On The Joini...mentioning
confidence: 93%
“…From the viewpoint of molding conditions, the higher cylinder temperature and higher injection speed increased lap shear strength. Pisanu et al [16] also reported that higher holding pressure, cylinder temperature and injection speed increased the joining strength.…”
Section: Influence Of Molding Conditions and Cnf Content On The Joini...mentioning
confidence: 93%
“…The tensile test standard used in this study was performed by citing the international test standard ISO 527-4, which defines test conditions for isotropic and orthotropic fiber-reinforced plastic composites. ISO 527-4 presents a standardized size for tensile testing of specimens (Pisanu et al, 2021). According to the above standard, the size of the test specimen was set as shown in Figure 1A.…”
Section: Test Specimenmentioning
confidence: 99%
“…High, biocorrosion-resistant adhesion of such hard coatings on the elastic TPU and controlled biofunctionality require adequate ion plasma pretreatment [ 31 , 32 , 33 ] and fluoridization or oxidation post-treatments [ 34 , 35 , 36 , 37 , 38 , 39 ]. The manufacturing of a fragile titanium is inserted with a flexibility that is based on the local mesh-width and thickness requires sophisticated high-precision milling and laser cutting [ 40 , 41 , 42 , 43 , 44 ], vacuum heat treatment to control the proper mechanical properties of the titanium, and surface finishing by electropolishing. The novelty and scientific contribution to the discipline comes from the development of materials in the form of thin coatings characterized by low hemocompatibility for long-term direct contact with blood for the desired application in the form of silent heart valves dedicated to the new generation of cardiac assist chambers.…”
Section: Introductionmentioning
confidence: 99%